An ecological study of Pteroma Pendula (Iepidoptera: Psychidae) in oil palm plantations with emphasis on the predatory activities of Oecophylla Smaragdina (hymenoptera: Formicidae) on the bagworm / Exelis Moise Pierre - Exelis, Moise Pierre (2013)
A study entitled “An ecological study of Pteroma pendula (Lepidoptera: Psychidae) in oil palm plantations with emphasis on the predatory activities of Oecophylla smaragdina (Hymenoptera: Formicidae) on the bagworm was conducted at the MPOB Research Plantation at Teluk Intan, Perak, Malaysia from 11.11.2010 to 31.01.2013. The main objectives of the study was to assess the infestation of P. pendula and investigate a correlation between pest density fluctuations with abiotic factors in the study area and to elucidate O. smaragdina occupancy pattern and its predatory behaviours towards P. pendula as well as assessing the productivity of palm trees occupied and not occupied by the weaver ants. Results of the survey showed that there was an infestation of the bagworm with peak outbreak from October to November 2010 which coincides with the ending of the dry season (Pearson correlation coefficient r = 0.474, p <0.05). O. smaragdina shows a high preference for tall trees where 92% of sampled palms were occupied with a Preference Index (Pi) of 1.84 but avoid short palms where none were occupied (Pi =0). Forty percent of the occupied palms harbours nests of various types ranging from 1-13 nest per palm with an average of 3.98 ±1.74 and uniquely the number was always odd. The weaver ants exhibited a bimodal foraging circadian cycle with two peaks: midday (12:00 h-15:00 h) and around dusk (17:30 h-18:30 h). O. smaragdina showed a moderate positive correlation of foraging activity with increase in air temperature (r=0.874, p < 0.001). However it is negatively correlated to relative humidity (r = - 0.921, p < 0.001). The attack tactic deployed by O. smaragdina towards the bagworm larva can be simplified into four main stages: Foraging and detection of prey; physical attack & securing of prey; piercing and releasing of formic acid and finally the lifting of paralyzed prey followed by transporting it to the nest. O. smaragdina shows no aggressive behavior towards Elaeidobius kamerunicus, the principal pollinators for oil palm. O. smaragdina had a high preference for pupae (Pi = 1.73) over larvae (Pi = 0.13) when the former was in abundance within the cut-off period of 90 minutes (U = 0; P < 0.01). A log-rank test demonstrated a statistically significant difference in survival ability between pupae and larvae (for equivalence death rates X2 = 3.42, d.f =1; P = 0.06). The degree of infestation by the bagworm was significantly different between the occupied and unoccupied palms (X2 = 406.30, d.f = 4, p < 0.001). Among the tall occupied palms, none were infested to Level 3 and 4 with 84% not infected at all (Level “0”). But 40% of the tall unoccupied palms were infested to Level 3 and 25% to Level 4. For the short unoccupied palms 31% were infested to Level 2 and 28% to Level 3 with only 2.2% showed no evidence of infestation. The degree of foliar injury is significantly less severe for the occupied palms (X2= 439.2), d.f = 4, p < 0.001). There is positive correlation between the level of infestation and the degree of foliar injury (rs= 0.952; d.f = 48; P < 0.01) in occupied palms and unoccupied palms (rs= 0.848; d.f = 48; P < 0.01). The productivity of DFB/FFB is significantly higher for the occupied palms (z ≥ 4.16, p < 0.0003) compare to shorter unoccupied palms. Similarly, the difference between tall occupied and tall unoccupied palms was highly significant at P < 0.002 (U=1). Based on ii the finding of this study, O. smaragdina holds a promising potential as biological control agent for the bagworm pests particularly against the increasing concern for sustainable oil palm industries.